PEMANFAATAN MICROSOFT OFFICE DALAM PENINGKATAN KAPASITAS PEMUDA YANG SIAP BEKERJA DI DUSUN IV KAMPUNG TOBA DESA SAWIT REJO - Ardin Dolok Saribu; Santoso Pasaribu; Novita Maywanty Hutajulu (Jurnal Abdimas Bina Bangsa, 2023)
The implementation of this service was motivated by our concern for the overseas children for the future of the teenagers in Hamlet IV, Toba Village, where we were born. The introduction and use of Microsoft office software is very useful for adolescents who are taking education from junior high school to college students, which with the knowledge of the use of the software will equip Toba village teenagers to be ready in the world of work. This training process went well and the youth were active in participating in each material explanation session and was followed by direct practice to implement each material presented. The team also provided 15 laptops plus personal laptops owned by the participants. Before the training started, we conducted a survey of 33 participants, it turned out that only 8 people knew Microsoft office software, while the rest still did not understand the use of the software. And after the training was completed, there was an increase in the number of participants who understood the use of the software to 28 people. The success of this training cannot be separated from the encouragement and motivation of the local government and parents